PENGARUH APLIKASI CANVA UNTUK MENINGKATKAN BERPIKIR KREATIF SISWA KELAS XII SMKS PLUS ULUMUL QURAN KUNIR SUBANG DALAM PEMBELAJARAN MENULIS ARTIKEL - Kusmayanti, Desti; MAULANA, IRPAN (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
In learning activities at school, especially in the Indonesian language subject, writing scientific articles is one of the skills that must be mastered by students. The use of learning media that stimulates students' interests and motivation can be used as a solution to improve creative thinking in writing articles. One of the various technological applications present in the world of education that can be used as a learning medium is Canva. This study uses quantitative research with a quasi-experimental design. At the end of the data analysis results, the researcher wanted to know the effect of the treatment that the researcher used on the experimental group. Therefore, the researcher used the N-Gain test with the help of SPSS version 20 to see if there was a difference between the experimental group using the Canva application and the control group that only used the group discussion model. The results showed that in the experimental group, the average N-Gain was 58.55, meaning> 40 with a high category, while in the control group, the average N-Gain was 11.17, meaning <40 with a low category. These results indicate that the ability to write articles using the Canva application stimulates students' creative thinking more than the group discussion model.